Effects of bidi smoking on all-cause mortality and cardiorespiratory outcomes in men from south Asia: an observational community-based substudy of the Prospective Urban Rural Epidemiology Study (PURE) - Dr. MyLinh Duong, MBBS; Sumathy Rangarajan, MSc; Xiaohe Zhang, MSc; Prof. Kieran Killian, PhD; Prem Mony, MD; Sumathi Swaminathan, PhD; Ankalmadagu Venkatsubbareddy Bharathi, PhD; Prof. Sanjeev Nair, MD; Prof. Krishnapillai Vijayakumar, MD; Indu Mohan, MD; Rajeev Gupta, PhD; Deepa Mohan, PhD; et al. (Elsevier, 2017)
Background: Bidis are minimally regulated, inexpensive, hand-rolled tobacco products smoked in south Asia. We examined the effects of bidi smoking on baseline respiratory impairment, and prospectively collected data for all-cause mortality and cardiorespiratory events in men from this region. Methods: This substudy of the international, community-based Prospective Urban Rural Epidemiology (PURE) study was done in seven centres in India, Pakistan, and Bangladesh. Men aged 35-70 years completed spirometry testing and standardised questionnaires at baseline and were followed up yearly. We used multilevel regression to compare cross-sectional baseline cardiorespiratory symptoms, spirometry measurements, and follow-up events (all-cause mortality, cardiovascular events, respiratory events) adjusted for socioeconomic status and baseline risk factors between non-smokers, light smokers of bidis or cigarettes (≤10 pack-years), heavy smokers of cigarettes only (>10 pack-years), and heavy smokers of bidis (>10 pack-years). Findings: 14 919 men from 158 communities were included in this substudy (8438 non-smokers, 3321 light smokers, 959 heavy cigarette smokers, and 2201 heavy bidi smokers). Mean duration of follow-up was 5·6 years (range 1-13). The adjusted prevalence of self-reported chronic wheeze, cough or sputum, dyspnoea, and chest pain at baseline increased across the categories of non-smokers, light smokers, heavy cigarette smokers, and heavy bidi smokers (p<0·0001 for association). Adjusted cross-sectional age-related changes in forced expiratory volume in 1 s (FEV1) and FEV1/forced vital capacity (FVC) ratio were larger for heavy bidi smokers than for the other smoking categories. Hazard ratios (relative to non-smokers) showed increasing hazards for all-cause mortality (light smokers 1·28 [95% CI 1·02-1·62], heavy cigarette smokers 1·59 [1·13-2·24], heavy bidi smokers 1·56 [1·22-1·98]), cardiovascular events (1·45 [1·13-1·84], 1·47 [1·05-2·06], 1·55 [1·17-2·06], respectively) and respiratory events (1·30 [0·91-1·85], 1·21 [0·70-2·07], 1·73 [1·23-2·45], respectively) across the smoking categories. Interpretation: Bidi smoking is associated with severe baseline respiratory impairment, all-cause mortality, and cardiorespiratory outcomes. Stricter controls and regulation of bidis are needed to reduce the tobacco-related disease burden in south Asia. Funding: Population Health Research Institute, Canadian Institutes of Health Research, and Heart and Stroke Foundation of Ontario.